Kontribusi Konseling Terhadap Kesehatan Mental : Systematic Literature Review - Saputra, Edy Cahya (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
Mental health plays an important role in maintaining the sustainability of individual life, including the ability to carry out social roles according to culture. This study aims to explore the literature on the contribution of counseling to individual mental health. The approach employed in this research is the Systematic Literature Review (SLR). The findings in this study indicate that counseling is effective in overcoming adolescent mental health problems and online counseling is more in demand because it provides comfort and convenience. Early adulthood individuals are more vulnerable to mental health disorders and need professional help or counselors to obtain mental health literacy as a basis for making decisions in dealing with mental health problems experienced. The conclusion that can be drawn in this study is that online counseling has proven to be effective and in demand in helping adolescents overcome mental health problems through professional support that increases literacy for appropriate decision making.